If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6c + -1) + -18 = 10c + 2 Reorder the terms: 2(-1 + 6c) + -18 = 10c + 2 (-1 * 2 + 6c * 2) + -18 = 10c + 2 (-2 + 12c) + -18 = 10c + 2 Reorder the terms: -2 + -18 + 12c = 10c + 2 Combine like terms: -2 + -18 = -20 -20 + 12c = 10c + 2 Reorder the terms: -20 + 12c = 2 + 10c Solving -20 + 12c = 2 + 10c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-10c' to each side of the equation. -20 + 12c + -10c = 2 + 10c + -10c Combine like terms: 12c + -10c = 2c -20 + 2c = 2 + 10c + -10c Combine like terms: 10c + -10c = 0 -20 + 2c = 2 + 0 -20 + 2c = 2 Add '20' to each side of the equation. -20 + 20 + 2c = 2 + 20 Combine like terms: -20 + 20 = 0 0 + 2c = 2 + 20 2c = 2 + 20 Combine like terms: 2 + 20 = 22 2c = 22 Divide each side by '2'. c = 11 Simplifying c = 11
| -4.905x^2-1.11x+0.8=0 | | 4x-13x-x=-150 | | 4(p+3)=4 | | -3(4x+1)+3x= | | 2m-2= | | 4-16p=(3-2p)4 | | c=5p+125 | | 5(6-7x)+14(4+4x)=275 | | 3x^2+2.5x-12.5=0 | | 2(3b+4)=8b-11 | | 5(x+9)-3=42 | | -w+3=53 | | -4(7b+5)=-76 | | -12+r+5-4=3r-1 | | 2(6)+5=8(6)+7 | | -12=2+5y+2y | | 23-1=d | | 8x^2+34x+15=0 | | 19=-4n-9 | | 11(12+14x)+15(14-5x)=263 | | 4x-3=5.01 | | 9-2a+2+2=6a+1-4a | | -1(4)=5-8 | | 3x+1-2x= | | 7(-x+-7)+8(x+8)=12 | | b+5=15 | | 1+2x-3=4x-2 | | a/7-3=-2 | | 2x+14-5=22 | | -4x=-4-3x | | 2(V+8)-4V=28 | | 70-x-x-2x=80 |